Diarrheagenic Escherichia coli Phylogroups Are Associated with Antibiotic Resistance and Duration of Diarrheal Episode - Mosquito, Susan (2015)
Conventionally, in Escherichia coli, phylogenetic groups A and B1 are associated with commensal strains while B2 and D are associated with extraintestinal strains. The aim of this study was to evaluate diarrheagenic (DEC) and commensal E. coli phylogeny and its association with antibiotic resistance and clinical characteristics of the diarrheal episode. Phylogenetic groups and antibiotic resistance of 369 E. coli strains (commensal strains and DEC from children with or without diarrhea) isolated from Peruvian children <1 year of age were determined by a Clermont triplex PCR and Kirby-Bauer method, respectively. The distribution of the 369 E. coli strains among the 4 phylogenetic groups was A (40%), D (31%), B1 (21%), and B2 (8%). DEC-control strains were more associated with group A while DEC-diarrhea strains were more associated with group D ( < 0.05). There was a tendency ( = 0.06) for higher proportion of persistent diarrhea (≥14 days) among severe groups (B2 and D) in comparison with nonsevere groups (A and B1). Strains belonging to group D presented significantly higher percentages of multidrug resistance than the rest of the groups ( > 0.01). In summary, DEC-diarrhea strains were more associated with group D than strains from healthy controls.